Human rights and mental health in post-apartheid South Africa: lessons from health care professionals working with suicidal inmates in the prison system - Jason Bantjes; Leslie Swartz; Pieter Niewoudt (BMC, 2017)
Abstract Background During the era of apartheid in South Africa, a number of mental health professionals were vocal about the need for socio-economic and political reform. They described the deleterious psychological and social impact of the oppressive and discriminatory Nationalist state policies. However, they remained optimistic that democracy would usher in positive changes. In this article, we consider how mental health professionals working in post-apartheid South Africa experience their work. Methods Our aim was to describe the experience of mental health professionals working in prisons who provide care to suicidal prisoners. Data were collected from in-depth semi-structured interviews and were analyzed using thematic content analysis. Results Findings draw attention to the challenges mental health professionals in post-apartheid South Africa face when attempting to provide psychological care in settings where resources are scarce and where the environment is anti-therapeutic. Findings highlight the significant gap between current policies, which protect prisoners' human rights, and every-day practices within prisons. Conclusions The findings imply that there is still an urgent need for activism in South Africa, particularly in the context of providing mental health care services in settings which are anti-therapeutic and inadequately resourced, such as prisons.